Aerosol-assisted Chemical Vapor Deposition of Metal Oxide Structures: Zinc Oxide Rods - Vallejos, Stella; Pizu Rova, Nade Z da; Čechal, Jan; Gràcia, Isabel; Cané, Carles (Journal of visualized experiments, 2017)
Whilst columnar zinc oxide (ZnO) structures in the form of rods or wires have been synthesized previously by different liquid- or vapor-phase routes, their high cost production and/or incompatibility with microfabrication technologies, due to the use of pre-deposited catalyst-seeds and/or high processing temperatures exceeding 900 °C, represent a drawback for a widespread use of these methods. Here, however, we report the synthesis of ZnO rods via a non-catalyzed vapor-solid mechanism enabled by using an aerosol-assisted chemical vapor deposition (CVD) method at 400 °C with zinc chloride (ZnCl2) as the precursor and ethanol as the carrier solvent. This method provides both single-step formation of ZnO rods and the possibility of their direct integration with various substrate types, including silicon, silicon-based micromachined platforms, quartz, or high heat resistant polymers. This potentially facilitates the use of this method at a large-scale, due to its compatibility with state-of-the-art microfabrication processes for device manufacture. This report also describes the properties of these structures (e.g., morphology, crystalline phase, optical band gap, chemical composition, electrical resistance) and validates its gas sensing functionality towards carbon monoxide.
Keywords: Aerosols; katalýza; aerosoly; oxid zinečnatý; Zinc Oxide; Catalysis